2021
DOI: 10.1093/ckj/sfab261
|View full text |Cite
|
Sign up to set email alerts
|

Associations between depressive symptoms and disease progression in older patients with chronic kidney disease: results of the EQUAL study

Abstract: Background Depressive symptoms are associated with adverse clinical outcomes in patients with end-stage kidney disease. Yet, few small studies have examined this association in patients with earlier phases of chronic kidney disease (CKD). We studied associations between baseline depressive symptoms and clinical outcomes in older patients with advanced CKD and examined whether these associations differed depending on sex. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Moreover, we observed that the associations of depression with hospitalization and mortality were more evident in men and in patients with eGFR ≥45 ml/min/1.73 m 2 . This sex difference has been previously reported [ 27 ], besides biological pathways, it may also be attributed to psychosocial aspects. For example, men are less likely to report mild depressive symptoms and have fewer help-seeking behaviors [ 43 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Moreover, we observed that the associations of depression with hospitalization and mortality were more evident in men and in patients with eGFR ≥45 ml/min/1.73 m 2 . This sex difference has been previously reported [ 27 ], besides biological pathways, it may also be attributed to psychosocial aspects. For example, men are less likely to report mild depressive symptoms and have fewer help-seeking behaviors [ 43 ].…”
Section: Discussionsupporting
confidence: 74%
“…A few previous studies have demonstrated a positive association between depression and CKD progression [ 17 , 23–25 ], whereas others have not [ 22 , 27 ]. There is notable heterogeneity in the definition of CKD progression across studies, where dialysis initiation was the most often used kidney endpoint, with a HR estimate ranging from 1.1 to 3.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the impressive study ‘Associations between depressive symptoms and disease progression in older patients with chronic kidney disease: results of the EQUAL study’ by Eveleens Maarse [ 1 ]. This study examined the associations between depression symptoms and clinical outcomes in older people (≥65 years of age) with chronic kidney disease (CKD) (eGFR ≤20 mL/min/1.73 m 2 ) and considered sex differences.…”
mentioning
confidence: 99%